Locus of Control and Job Satisfaction on Employee Performance, Mediated by Organizational Citizenship Behavior among the Working Staff in the Accounting Department - Ermina Rusilawati; Intan Purnama; Dominicus Josephus Swanto Tjahjana; Wan Muhamad Kudri (Institut Bisnis dan Teknologi Pelita Indonesia, 2023)
This research aims to investigate the impact of Locus of Control and Job Satisfaction on Organizational Citizenship Behavior (OCB) and Employee Performance. It also aims to explore the role of OCB as a mediating variable in the relationship between Locus of Control, Job Satisfaction, and Employee Performance among personnel in the Accounting Department of Panca Eka Pekanbaru (Naval Base V Pekanbaru). The research design adopts a causal approach with a quantitative methodology. The sampling method employed is saturated sampling, and primary data is collected through a questionnaire. Data analysis is conducted using the Partial Least Square method. The study involves fifty accounting staff members from Panca Eka Pekanbaru. Evaluating Organizational Citizenship Behavior (OCB) in the accounting staff is crucial due to its significance in defining the responsibilities of Navy personnel across different units. Job Satisfaction also plays a vital role in enhancing work performance. The accounting department of Panca Eka Pekanbaru emphasizes the importance of optimal employee performance. This emphasis is rooted in the perspective of the accounting staff regarding their control over internal and external events in their lives. The findings of the study are as follows: (1) Locus of Control does not significantly affect Organizational Citizenship Behavior (OCB); (2) Job Satisfaction positively influences Organizational Citizenship Behavior (OCB); (3) Both Locus of Control and Job Satisfaction have an impact on Employee Performance; (4) Organizational Citizenship Behavior (OCB) does not significantly influence Employee Performance; (5) Locus of Control and Job Satisfaction do not significantly affect Employee Performance through the mediating role of Organizational Citizenship Behavior (OCB).